Arsenic-iron-based alloy with high performance and stable compression resistance and preparation method
By adding chromium powder to the arsenic iron powder and ball milling and vacuum hot pressing sintering, a high-performance compressive stability arsenic iron-based alloy was prepared, which solved the problem of difficulty in reducing the leaching toxicity of arsenic iron-based alloy in the prior art, and achieved efficient improvement of compressive strength and reduction of leaching toxicity.
Patent Information
- Application Number
- CN202411732928.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
AI Technical Summary
The existing arsenic iron-based alloys still have certain leaching toxicity based on the incorporation of exogenous metals and the improvement of compressive strength, and it is difficult to effectively reduce the leaching toxicity of arsenic.
By adding chromium powder to the arsenic iron powder, ball milling and vacuum hot pressing sintering treatment, a high-performance, compressive and stable arsenic iron-based alloy was prepared. This method not only improves compressive strength, but also significantly reduces the leaching toxicity of arsenic.
On the basis of improving the compressive strength, the leaching toxicity of arsenic iron-based alloy is significantly reduced, ensuring that the alloy still has excellent hardness and compressive strength after TCLP leaching, and shows high corrosion resistance.
Smart Images

Figure CN119530592A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of alloys, and in particular relates to a high-performance, compressive and stable arsenic-iron based alloy and a preparation method thereof. Background Art
[0002] The main sources of arsenic pollution include the mining and smelting of arsenic compounds, the development and smelting of non-ferrous metals, the widespread use of arsenic compounds, and the burning of coal. Arsenic can generally enter the human body through water, air, and food, causing harm. Long-term exposure to arsenic in drinking water and food can cause cancer and skin lesions. The lowest concentration of arsenic that is toxic to crops is 3 mg / L, and it is also very toxic to aquatic organisms. Therefore, it is particularly important to utilize arsenic as a resource and reduce its leaching toxicity.
[0003] The Chinese invention patent application with publication number CN118374711A discloses a high-strength, high-hardness, high-density arsenic-based alloy and a preparation method thereof; it is based on arsenic-iron mixed powder and provides cobalt as an exogenous metal, thereby preparing an arsenic-iron alloy doped with cobalt. Although it utilizes arsenic as a resource and can obtain an arsenic-based alloy with higher compressive strength; however, the applicant has found that it still has certain leaching toxicity.
[0004] In view of this, it is necessary to provide a high-performance, compressively stable arsenic-iron-based alloy and a preparation method to solve or at least alleviate the technical defects of how to reduce leaching toxicity on the basis of incorporating exogenous metals and improving compressive strength. Summary of the invention
[0005] The main purpose of the present invention is to provide a high-performance, compressive and stable arsenic-iron based alloy and a preparation method, aiming to solve or at least alleviate the technical problem of how to reduce leaching toxicity on the basis of incorporating exogenous metals and improving compressive strength.
[0006] To achieve the above object, the present invention provides a method for preparing a high-performance, compressive-resistant and stable arsenic-iron-based alloy, comprising the steps of:
[0007] S1, providing a mixture; the mixture comprises arsenic iron powder and chromium powder, the arsenic iron powder comprises arsenic powder and iron powder; the mass percentage of the chromium powder and the arsenic iron powder is not less than 4%;
[0008] S2, ball milling the mixture under the protection of an inert atmosphere to obtain a ball milling product; the ball milling time is not less than 8 hours;
[0009] S3, vacuum hot pressing and sintering the ball milled product to obtain an arsenic-iron based alloy; the vacuum hot pressing and sintering comprises: in a vacuum environment, heating the ball milled product to 350-500°C for a heat preservation time of not less than 0.3h; then, heating the ball milled product to 600-850°C for a heat preservation time of not less than 0.5h; and, during the vacuum hot pressing and sintering process, applying a pressure of 25-50MPa to the ball milled product.
[0010] Furthermore, the mass percentage of the chromium powder and the ferroarsenic powder is not less than 15%.
[0011] Furthermore, the mass percentage of the chromium powder and the ferroarsenic powder is not less than 20%.
[0012] Furthermore, the mass percentage of the chromium powder and the ferroarsenic powder is 4-21%.
[0013] Furthermore, the mass percentage of the chromium powder and the ferroarsenic powder is 14-21% or 19-21%.
[0014] Furthermore, the molar ratio of the arsenic powder to the iron powder is 0.1 to 2:1.
[0015] Furthermore, the rotation speed of the ball mill is 250-400 r / min, and the duration of the ball mill is 8-48 h.
[0016] Furthermore, the ball-to-material ratio of the ball mill is 10 to 22:1; the particle size of the grinding balls used in the ball mill includes one or more of 3 mm, 6 mm, 10 mm and 15 mm.
[0017] The present invention also provides a high-performance, compressive-resistant and stable arsenic-iron-based alloy, which is prepared by any of the preparation methods described above.
[0018] Furthermore, the phases in the arsenic-iron based alloy include iron-chromium solid solution phase and FeAs.
[0019] Compared with the prior art, the present invention has at least the following advantages:
[0020] The present invention reduces the leaching toxicity of the arsenic-iron-based alloy on the basis of adding exogenous metallic chromium and improving the compressive strength; specifically, compared with the arsenic-iron-based alloy without adding exogenous metal, the present invention can greatly improve the compressive strength of the arsenic-iron-based alloy by adding chromium powder to the arsenic-iron powder; and even if the amount of arsenic added is relatively high, the arsenic-iron-based alloy in the present invention still has extremely low TCLP arsenic leaching toxicity.
[0021] Although the arsenic-iron-based alloy doped with Co can improve the performance of the arsenic-iron-based alloy; however, compared with the arsenic-iron-based alloy doped with Co in the arsenic-iron powder, the present invention can not only realize the resource utilization of Cr by adding Cr, but also further improve the compressive strength and solve the leaching toxicity problem that the Co-doped powder has not completely solved; the addition of Cr powder in the present invention can also reduce the leaching of Fe and will not cause the problem of Cr leaching.
[0022] The arsenic-iron-based alloy of the present invention can still have excellent hardness and compressive strength after TCLP leaching; in the present invention, the arsenic-iron-based alloy can maintain a high compressive strength before and after leaching; and adding a certain content of Cr element to the alloy helps to improve the hardness stability of the alloy; therefore, the arsenic-iron-based alloy obtained by the present invention can still maintain high mechanical properties and a low arsenic leaching concentration (<5 mg / L) after TCLP leaching, showing high corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0024] Figure 1 is the SEM-BSE image of the As-Fe-5Cr alloy (5Cr) in Example 1 of the present invention; (a) refers to the SEM-BSE image, SE corresponds to the SEM image, BSE corresponds to the BSE image, (a 1 ) corresponds to the element analysis at spot1, (a 2 ) corresponds to the element analysis at spot2;
[0025] Figure 2 is the SEM-BSE image of the As-Fe-10Cr alloy (10Cr) in Example 2 of the present invention; (a) refers to the SEM-BSE image, SE corresponds to the SEM image, BSE corresponds to the BSE image, (a 1 ) corresponds to the element analysis at spot1, (a 2 ) corresponds to the element analysis at spot2;
[0026] Figure 3 is the SEM-BSE image of the As-Fe-15Cr alloy (15Cr) in Example 3 of the present invention; (a) refers to the SEM-BSE image, SE corresponds to the SEM image, BSE corresponds to the BSE image, (a 1 ) corresponds to the element analysis at spot1, (a 2) corresponds to the element analysis at spot2;
[0027] Figure 4 is the SEM-BSE image of the As-Fe-20Cr alloy (20Cr) in Example 4 of the present invention; (a) refers to the SEM-BSE image, SE corresponds to the SEM image, BSE corresponds to the BSE image, (a 1 ) corresponds to the element analysis at spot1, (a 2 ) corresponds to the element analysis at spot2;
[0028] Figure 5 It is the SEM-BSE image of the As-Fe alloy (0Cr) in Comparative Example 1 of the present invention; (a) refers to the SEM-BSE image, SE corresponds to the SEM image, BSE corresponds to the BSE image, (a 1 ) corresponds to the element analysis at spot1, (a 2 ) corresponds to the element analysis at spot2;
[0029] Figure 6 The XRD results of the arsenic-iron-based alloys in Examples 1-4 of the present invention and Comparative Example 1; 0Cr corresponds to the arsenic-iron-based alloy in Comparative Example 1, 5Cr corresponds to the arsenic-iron-based alloy in Example 1, 10Cr corresponds to the arsenic-iron-based alloy in Example 2, 15Cr corresponds to the arsenic-iron-based alloy in Example 3, and 20Cr corresponds to the arsenic-iron-based alloy in Example 4;
[0030] Figure 7 The density results of the arsenic-iron-based alloys in Examples 1-4 of the present invention and Comparative Example 1; 0Cr corresponds to the arsenic-iron-based alloy in Comparative Example 1, 5Cr corresponds to the arsenic-iron-based alloy in Example 1, 10Cr corresponds to the arsenic-iron-based alloy in Example 2, 15Cr corresponds to the arsenic-iron-based alloy in Example 3, and 20Cr corresponds to the arsenic-iron-based alloy in Example 4;
[0031] Figure 8 The compressive strength results of the arsenic-iron-based alloys in Examples 1-4 of the present invention and Comparative Example 1; 0Cr corresponds to the arsenic-iron-based alloy in Comparative Example 1, 5Cr corresponds to the arsenic-iron-based alloy in Example 1, 10Cr corresponds to the arsenic-iron-based alloy in Example 2, 15Cr corresponds to the arsenic-iron-based alloy in Example 3, and 20Cr corresponds to the arsenic-iron-based alloy in Example 4;
[0032] Fig. 9 The hardness results of the arsenic-iron-based alloys in Examples 1-4 of the present invention and Comparative Example 1; 0Cr corresponds to the arsenic-iron-based alloy in Comparative Example 1, 5Cr corresponds to the arsenic-iron-based alloy in Example 1, 10Cr corresponds to the arsenic-iron-based alloy in Example 2, 15Cr corresponds to the arsenic-iron-based alloy in Example 3, and 20Cr corresponds to the arsenic-iron-based alloy in Example 4;
[0033] Fig.10 The TCLP leaching toxicity evaluation of the arsenic-iron based alloys in Examples 1-4 of the present invention and Comparative Example 1 is shown; 0Cr corresponds to the arsenic-iron based alloy in Comparative Example 1, 5Cr corresponds to the arsenic-iron based alloy in Example 1, 10Cr corresponds to the arsenic-iron based alloy in Example 2, 15Cr corresponds to the arsenic-iron based alloy in Example 3, and 20Cr corresponds to the arsenic-iron based alloy in Example 4;
[0034] Fig.11 is the compressive strength of the arsenic-iron-based alloy after TCLP leaching in Examples 1-4 of the present invention and Comparative Example 1; 0Cr corresponds to the arsenic-iron-based alloy in Comparative Example 1, 5Cr corresponds to the arsenic-iron-based alloy in Example 1, 10Cr corresponds to the arsenic-iron-based alloy in Example 2, 15Cr corresponds to the arsenic-iron-based alloy in Example 3, and 20Cr corresponds to the arsenic-iron-based alloy in Example 4;
[0035] Fig.12 is the hardness of the arsenic-iron-based alloy after TCLP leaching in Examples 1-4 of the present invention and Comparative Example 1; 0Cr corresponds to the arsenic-iron-based alloy in Comparative Example 1, 5Cr corresponds to the arsenic-iron-based alloy in Example 1, 10Cr corresponds to the arsenic-iron-based alloy in Example 2, 15Cr corresponds to the arsenic-iron-based alloy in Example 3, and 20Cr corresponds to the arsenic-iron-based alloy in Example 4;
[0036] Fig.13 The TCLP leaching toxicity evaluation of the arsenic-iron based alloy in Example 4 of the present invention and Comparative Example 2 is shown; 20Cr corresponds to the arsenic-iron based alloy in Example 4; 20Co corresponds to the arsenic-iron based alloy in Comparative Example 2.
[0037] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with the implementation methods and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Furthermore, the technical solutions between the various embodiments of the present invention may be combined with each other, but this must be based on the fact that they can be implemented by ordinary technicians in the field. When the combination of technical solutions is mutually contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0040] When the embodiments give a numerical range, it should be understood that, unless otherwise specified in the present invention, the two endpoints of each numerical range and any value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention and the technical personnel in this field of technology have mastered the prior art and recorded the present invention. Any method, equipment and material of the prior art similar or equivalent to the method, equipment and material in the embodiments of the present invention can also be used to implement the present invention. It should be noted that in the patent with publication number CN115491534A, the compressive strength is 140Mpa, indicating that its compressive strength can reach the standard of 140Mpa, and its actual compressive strength is greater than the standard of 140Mpa; it should also be noted that the leaching concentration of the element will be different in different leaching methods, and the comparison of leaching concentrations needs to be carried out in the same leaching method.
[0041] The present invention provides a method for preparing a high-performance, compressive-resistant and stable arsenic-iron-based alloy, comprising the steps of:
[0042] S1, providing a mixture, wherein the mixture includes arsenic iron powder and chromium powder, and the arsenic iron powder includes arsenic powder and iron powder; the present invention adds chromium powder to the arsenic iron powder and prepares the alloy, which can not only greatly improve the compressive strength, but also reduce the leaching toxicity of arsenic, and the leaching toxicity of chromium is also low.
[0043] In the present invention, the purity of the chromium powder, the iron powder, and the arsenic powder is not less than 98wt.%; specifically, the purity of the chromium powder can be not less than 99wt.%, the purity of the iron powder can be not less than 99.5wt.%, and the purity of the arsenic powder can be not less than 98wt.%. In order to realize the resource utilization and high-value treatment of solid waste, each metal powder in the present invention can be derived from the corresponding metal waste slag; the arsenic powder can be obtained from arsenic slag, and the chromium powder can be obtained from chromium slag.
[0044] In the present invention, the mass percentage of the chromium powder and the arsenic iron powder is not less than 4% or not less than 5%; further, the mass percentage of the chromium powder and the arsenic iron powder is not less than 15%; further, the mass percentage of the chromium powder and the arsenic iron powder is not less than 20%. When the mass percentage of the chromium powder and the arsenic iron powder is not less than 4%, the compressive strength is significantly improved and the leaching toxicity is reduced compared with the undoped chromium powder; when the mass percentage of the chromium powder and the arsenic iron powder is not less than 20%, the performance is further improved and the leaching toxicity is further reduced.
[0045] As another embodiment, the mass percentage of the chromium powder and the arsenic iron powder is 4-21%. The mass percentage of the chromium powder and the arsenic iron powder is 14-21% or 15-21% or 19-21%. When the mass percentage of the chromium powder and the arsenic iron powder is 19-21%, not only the leaching toxicity is lower and the compressive strength is higher, but also the hardness of the arsenic iron-based alloy block after TCLP leaching is still high or even higher.
[0046] Combined with the comprehensive comparison of Examples 1-4 of the present application, the results of the Cr-containing alloy block show that the addition of high Cr content promotes the formation of FeAs phase, and the Cr element is enriched in the FeAs phase, while in the FeAs 2 Look poor.
[0047] In the present invention, the amount of arsenic powder added can be relatively large; taking Examples 1-4 as an example, the molar ratio of the arsenic powder to the iron powder actually reaches 0.6:0.4; as an illustration, in the present invention, the molar ratio of the arsenic powder to the iron powder can be 0.1-2:1; further, the molar ratio of the arsenic powder to the iron powder is 0.1-0.35:1 or 0.35-2:1; further, the molar ratio of the arsenic powder to the iron powder is 1-2:1. In the present invention, the molar ratio of the arsenic powder to the iron powder refers to the molar ratio of arsenic element to iron element; since the arsenic powder and iron powder used in the present invention have high purity, the present invention can directly record the arsenic powder as arsenic element and the iron powder as iron element.
[0048] S2, ball-milling the mixture under the protection of an inert atmosphere to obtain a ball-milled product; the ball-milling time is not less than 8 hours.
[0049] In the present invention, the rotation speed of the ball mill is 250-400r / min or 300-400r / min, and the duration of the ball milling is 8-48h or 30-48h. The ball-to-material ratio of the ball mill is 10-22:1 or 10-20:1 or 18-22:1; the particle size of the grinding balls used in the ball mill can include one or more of 3mm, 6mm, 10mm and 15mm; the grinding balls used in the ball mill can specifically be grinding balls with a particle size of 6mm and a particle size of 10mm, and the weight ratio of the two can be 0.8-1.2:0.8-1.2. During the ball milling process, the continuous operation is paused for 3-15min after 20-60min, or the continuous operation is paused for 4-6min after 20-40min.
[0050] The vacuum ball mill liner used in the ball milling process of the present invention can be made of stainless steel, corundum or hard alloy; the grinding ball can be made of stainless steel, corundum or hard alloy; in the present invention, the inert gas can include or be at least one of argon and nitrogen.
[0051] S3, vacuum hot pressing and sintering the ball milled product to obtain an arsenic-iron based alloy; the vacuum hot pressing and sintering comprises: in a vacuum environment, heating the ball milled product to 350-500°C for a holding time of not less than 0.3h (may be 0.3-1h), then heating the ball milled product to 600-850°C for a holding time of not less than 0.5h (may be 0.5-1.5h); during the vacuum hot pressing and sintering process, applying a pressure of 25-50MPa to the ball milled product.
[0052] Specifically, the vacuum hot pressing sintering includes: placing the ball milled product in a vacuum environment; then, sintering the ball milled product, and applying a pressure of 25 to 50 MPa to the ball milled product during the sintering process.
[0053] The sintering process includes: raising the temperature of the ball-milled product to 350-500° C. and keeping the temperature for 0.3-1 hour; then, raising the temperature of the ball-milled product to 600-850° C. and keeping the temperature for 0.5-1.5 hours; after the sintering is completed, cooling the product to room temperature with the furnace.
[0054] Furthermore, the vacuum hot pressing sintering includes: in a vacuum environment, heating the ball milling product to 350-450°C for a holding time of 0.3-6 hours, and then heating the ball milling product to 750-850°C for a holding time of 0.8-1.2 hours; during the vacuum hot pressing sintering process, applying a pressure of 25-35 MPa to the ball milling product. The heating rate of the vacuum hot pressing sintering can be 8-12°C / min, and the pressure increase rate can be 0.4-0.6 MPa / s.
[0055] The present invention also provides a high-performance, compressive and stable arsenic-iron-based alloy, which is prepared by any of the above-mentioned preparation methods. The phases in the arsenic-iron-based alloy include an iron-chromium solid solution phase and FeAs, and the arsenic-iron-based alloy has a uniform FeAs phase; or the phases in the arsenic-iron-based alloy include an iron-chromium solid solution phase, FeAs and FeAs 2 .
[0056] The compressive strength of the arsenic-iron based alloy can be 1300-1450.62 MPa, the hardness can be 800-808.33 HV0.5, and the density can be 7.2-7.283 g / cm 3 ; In the arsenic-iron based alloy, the TCLP leaching concentration of arsenic can be less than 5 mg / L (e.g. 4.41-4.5 mg / L), the TCLP leaching concentration of iron can be less than 4 mg / L (e.g. 3.51-3.9 mg / L), and the TCLP leaching concentration of chromium can be less than 0.1 mg / L (e.g. 0.075-0.09 mg / L).
[0057] Specifically, based on the technical role of chromium powder in this application, the arsenic-iron-based alloy can achieve a maximum compressive strength of 1450.62MPa at room temperature, a Vickers hardness of 808.33HV0.5, and a density of 7.283g / cm 3 The arsenic-iron based alloy obtained by the present invention is leached by TCLP method, and the arsenic leaching concentration is low (<5 mg / L), showing high environmental stability.
[0058] The following are specific examples of the present invention:
[0059] The performance test method used in the present invention is:
[0060] Density: AKD-220A touch screen high-precision solid density tester, using Archimedes principle buoyancy method to measure the density of arsenic-iron based alloy in each embodiment;
[0061] Compressive strength: tested by electronic universal testing machine;
[0062] The compressive strength in the present invention is the compressive strength at room temperature; the test is carried out using an electronic universal material testing machine, and the strain rate is set to 0.3 mm min -1 Before the test, the surface of the alloy block sample needs to be polished with sandpaper of different mesh sizes (800 mesh, 1000 mesh, 2000 mesh) to eliminate surface scratches and ensure a smooth surface. For each group of compressive strength tests, three parallel samples are prepared, and the average value is taken as the compressive strength data of the group.
[0063] Hardness test: Tested with Vickers hardness tester.
[0064] Leaching toxicity test (TCLP method): Acetic acid was used to evaluate the leaching toxicity of the alloy block obtained by vacuum hot pressing sintering.
[0065] The experimental process of TCLP leaching toxicity test is as follows: accurately weigh the alloy block with an electronic balance, put it into a 50mL centrifuge tube, and add the leaching agent under the condition of liquid-solid ratio of 20mL / g; dilute analytical pure acetic acid with ultrapure water to pH 2.64±0.05 to obtain the leaching agent. Perform tumbling oscillation at room temperature for 18h±2h, and the oscillation speed is 30±2r min -1 After the oscillation, the leached solution was filtered through a 0.45 μm filter head to obtain the filtrate to be tested, and then the concentration of the elements in the filtrate was determined by ICP-OES.
[0066] Example 1
[0067] 1. Mix chromium powder with a purity of 99wt.%, iron powder with a purity of 99.5wt.% and arsenic powder with a purity of 98wt.% to obtain a mixture (first mix the arsenic powder and the iron powder to obtain arsenic-iron powder, and then mix the chromium powder into the arsenic-iron powder); put the mixture into a vacuum ball mill, and the gas in the vacuum ball mill is argon.
[0068] The molar ratio of arsenic powder to iron powder is 0.6:0.4, and the mass percentage of chromium powder to arsenic iron powder is 5% (ie, the added amount of chromium powder is 5wt.% of the total mass of arsenic iron powder).
[0069] 2. Place the above-mentioned vacuum ball mill on a high-energy planetary ball mill. The lining material of the vacuum ball mill is stainless steel, the grinding balls are stainless steel, the grinding balls are 6mm and 10mm grinding balls distributed in a weight ratio of 1:1, and the ball-to-material ratio is 20:1. The mechanical alloying reaction is carried out at a rotation speed of 340r / min. During the reaction process, it runs continuously for 30min and then pauses for 5min. The reaction time is 40h (including the pause time). After the mechanical alloying reaction is completed, take out the sample (ball milling product).
[0070] 3. Place the obtained sample (ball milling product) into a vacuum hot pressing sintering furnace mold and evacuate and maintain the vacuum for 20 minutes to avoid the presence of oxygen.
[0071] Subsequently, the vacuum hot pressing sintering furnace was controlled to perform vacuum hot pressing sintering on the sample according to the following settings:
[0072] The temperature was raised to 400°C at a rate of 10°C / min and kept at that temperature for 30 min, then raised to 800°C at a rate of 10°C / min and kept at that temperature for 60 min, and finally cooled to room temperature with the furnace;
[0073] When controlling the temperature, the pressure was synchronously controlled to rise to 30MPa at a rate of 0.5MPa / s and maintained for 160min, and finally dropped to room pressure at a rate of 0.5MPa / s;
[0074] When the temperature is cooled to room temperature and the pressure is reduced to room pressure (no longer applied pressure), the arsenic-iron based alloy in this embodiment is obtained, which is recorded as As-Fe-5Cr alloy (5Cr alloy).
[0075] In this embodiment, the SEM-BSE image of the arsenic-iron alloy (As-Fe-5Cr) block is shown in Figure 1 As shown, it can be seen from the SEM image that there are a large number of continuous holes on the surface of the As-Fe-5Cr alloy block. The BSE image shows that there are two regional distributions with different contrasts, one is a dark gray area, and the other is a grayish white area with obvious regional distribution.
[0076] In this embodiment, see Figure 6 As shown, As-Fe-5Cr alloy is composed of FeAs2 The characteristic peaks of the phase are dominant.
[0077] In this embodiment, see Figure 7 As shown, the density of As-Fe-5Cr alloy is 7.188 g / cm 3 .
[0078] In this embodiment, see Figure 8 As shown, the compressive strength of As-Fe-5Cr alloy is 1100.30MPa.
[0079] In this embodiment, see Fig. 9 As shown, the hardness of As-Fe-5Cr alloy is 834.17HV0.5.
[0080] In this embodiment, see Fig.10 As shown in Table 1, the TCLP leaching concentrations of arsenic, iron, and chromium in the As-Fe-5Cr alloy are 88.10 mg / L, 64.74 mg / L, and 0.160 mg / L, respectively.
[0081] In this embodiment, the compressive strength of the As-Fe-5Cr alloy after TCLP leaching is shown in Fig.11 As shown; after TCLP leaching, the hardness of As-Fe-5Cr alloy is shown in Fig.12 shown.
[0082] Example 2
[0083] Compared with Example 1, the addition amount of chromium powder in this example is adjusted so that the mass percentage of chromium powder and arsenic iron powder is 10%, and other conditions remain unchanged, thereby obtaining the arsenic iron-based alloy in this example, which is recorded as As-Fe-10Cr alloy (10Cr alloy).
[0084] In this embodiment, the SEM-BSE image of the As-Fe-10Cr alloy is shown in FIG. Figure 2 As shown in the figure, it can be seen from the SEM that the number of pores on the surface of the As-Fe-10Cr alloy block decreases as the Cr content in the alloy block increases to 10wt.%, and the number of pores on the surface decreases and tends to be flat. From the BSE diagram and the Mapping test results, it can be found that the phase in the alloy has not changed significantly.
[0085] In this embodiment, see Figure 6 As shown, As-Fe-10Cr alloy is still FeAs 2 The characteristic peaks of the phase are dominant, which further verifies the BSE results.
[0086] In this embodiment, see Figure 7 As shown, the density of As-Fe-10Cr alloy is 7.140 g / cm3 .
[0087] In this embodiment, see Figure 8 As shown, the compressive strength of As-Fe-10Cr alloy is 1180.34MPa.
[0088] In this embodiment, see Fig. 9 As shown, the hardness of As-Fe-10Cr alloy is 688.81HV0.5.
[0089] In this embodiment, see Fig.10 As shown in Table 1, the leaching concentrations of arsenic, iron and chromium in the As-Fe-10Cr alloy are 23.01 mg / L, 15.55 mg / L and 0.228 mg / L, respectively.
[0090] In this embodiment, the compressive strength of the As-Fe-10Cr alloy after TCLP leaching is shown in Fig.11 As shown; after TCLP leaching, the hardness of As-Fe-10Cr alloy is shown in Fig.12 shown.
[0091] Example 3
[0092] Compared with Example 1, the amount of chromium powder added in this example is adjusted so that the mass percentage of chromium powder and arsenic iron powder is 15%, and other conditions remain unchanged, thereby obtaining the arsenic iron-based alloy in this example, which is recorded as As-Fe-15Cr alloy (15Cr alloy).
[0093] In this embodiment, the SEM-BSE image of the As-Fe-15Cr alloy is shown in FIG. Figure 3 As shown in the SEM-BSE image, it can be seen that the number of pores on the surface of the As-Fe-15Cr alloy block is further reduced, the surface presents a smooth and flat structure, and the dark gray area (FeAs phase) is further increased.
[0094] In this embodiment, see Figure 6 As shown in Figure 1, the phase transformation of As-Fe-15Cr alloy is dominated by the characteristic peak of FeAs phase. 2 The intensity of the phase peak weakened sharply, indicating that its phase content showed a downward trend.
[0095] In this embodiment, see Figure 7 As shown, the density of As-Fe-15Cr alloy is 7.137 g / cm 3 .
[0096] In this embodiment, see Figure 8 As shown, the compressive strength of As-Fe-15Cr alloy is 1288.34MPa.
[0097] In this embodiment, see Fig. 9 As shown, the hardness of As-Fe-15Cr alloy is 729.90HV0.5.
[0098] In this embodiment, see Fig.10 As shown in Table 1, the leaching concentrations of arsenic, iron and chromium in the As-Fe-15Cr alloy are 13.73 mg / L, 9.47 mg / L and 0.160 mg / L, respectively.
[0099] In this embodiment, the compressive strength of the As-Fe-15Cr alloy after TCLP leaching is shown in Fig.11 As shown; after TCLP leaching, the hardness of As-Fe-15Cr alloy is shown in Fig.12 shown.
[0100] Example 4
[0101] Compared with Example 1, the amount of chromium powder added in this example is adjusted so that the mass percentage of chromium powder and arsenic iron powder is 20%, and other conditions remain unchanged, thereby obtaining the arsenic iron-based alloy in this example, which is recorded as As-Fe-20Cr alloy (20Cr alloy).
[0102] In this embodiment, the SEM-BSE image of the As-Fe-20Cr alloy is shown in FIG. Figure 4 As shown, it can be seen from the SEM-BSE image that when the Cr element content in the alloy block increases to 20wt.%, there are no large pores on the surface of the As-Fe-20Cr alloy block, and mainly micropores exist; the BSE image shows only one dark gray area, indicating that the alloy block forms a single uniform phase.
[0103] Combined with the EDS spectrum results, it was found that the ratio of As to Fe elements in the alloy block was close to 1:1, indicating that it was mainly composed of FeAs phase and was evenly distributed; the Cr content was very close to the designed composition.
[0104] In this embodiment, see Figure 6 As shown, the As-Fe-20Cr alloy phase is mainly composed of the characteristic peak of the FeAs phase, and the characteristic peak of the Cr element with a weaker signal is detected. This may be due to the presence of incompletely reacted Cr powder caused by the excessive addition of Cr content.
[0105] In this embodiment, see Figure 7 As shown, the density of As-Fe-20Cr alloy is 7.283 g / cm 3 .
[0106] In this embodiment, see Figure 8 As shown, the compressive strength of As-Fe-20Cr alloy is 1450.62MPa.
[0107] In this embodiment, see Fig. 9 As shown, the hardness of As-Fe-20Cr alloy is 808.33HV0.5.
[0108] In this embodiment, see Fig.10 As shown in Table 1, the leaching concentrations of arsenic, iron and chromium in the As-Fe-20Cr alloy are 4.41 mg / L, 3.51 mg / L and 0.075 mg / L, respectively.
[0109] In this embodiment, the compressive strength of the As-Fe-20Cr alloy after TCLP leaching is shown in Fig.11 As shown; after TCLP leaching, the hardness of As-Fe-20Cr alloy is shown in Fig.12 shown.
[0110] Comparative Example 1
[0111] Compared with Example 1, in this comparative example, no chromium powder is added (arsenic iron powder is directly used as a mixed material), and other conditions remain unchanged, thereby obtaining the arsenic iron-based alloy in this comparative example, which is recorded as As-Fe alloy (0Cr alloy).
[0112] In this comparative example, the SEM-BSE image of the As-Fe alloy is shown in Figure 5 As shown in the SEM, it can be seen that the surface of the alloy block is almost microporous, with no obvious aggregation phenomenon, showing a more uniform and dense microstructure. The BSE map in the alloy block does not show obvious regional distribution, but combined with Figure 6 The XRD results show that the arsenic-iron based alloy without chromium powder has FeAs phase and FeAs 2 Mutually.
[0113] In this comparative example, see Figure 6 As shown, As-Fe alloys show FeAs and FeAs 2 The characteristic peaks of FeAs 2 The peak is more obvious.
[0114] In this comparative example, see Figure 7 As shown, the density of As-Fe alloy is 7.412 g / cm 3 .
[0115] In this comparative example, see Figure 8 As shown, the compressive strength of As-Fe alloy is 674.74MPa.
[0116] In this comparative example, see Fig. 9 As shown, the hardness of As-Fe alloy is 899.41HV0.5.
[0117] In this comparative example, see Fig.10 As shown in Table 1, the leaching concentrations of arsenic and iron in the As-Fe alloy are 179.38 mg / L and 148.59 mg / L, respectively.
[0118] In this comparative example, the compressive strength of the As-Fe alloy after TCLP leaching is shown in Fig.11 As shown; after TCLP leaching, the hardness of As-Fe alloy is shown in Fig.12 shown.
[0119] Comparative Example 2
[0120] Compared with Example 4, in this comparative example, the chromium powder is adjusted to cobalt powder, and other conditions remain unchanged, to obtain the arsenic-iron based alloy in this comparative example, which is recorded as As-Fe-20Co alloy (20Co alloy).
[0121] In this comparative example, see Fig.13 As shown in the figure, after TCLP leaching, the leaching concentrations of As, Fe and Co elements in the As-Fe-20Co alloy block are 104.79 mg / L, 51.39 mg / L and 33.18 mg / L, respectively, and the leached element concentrations are relatively high.
[0122] However, after TCLP leaching of the arsenic-iron based alloy in Example 4 of the present invention, the concentrations of As, Fe and Cr in the As-Fe-20Cr ternary alloy block leachate were only 4.41 mg / L, 3.51 mg / L and 0.075 mg / L, and the concentration of the leached elements was significantly reduced.
[0123] Analysis example 1
[0124] 1. Combined with the density test results, it can be seen that the actual density of the As-Fe-xCr (x=5, 10, 15, 20wt.%) ternary alloy block shows a trend of first decreasing and then increasing with the increase of Cr content. This phenomenon may be attributed to the changes in morphology and phase in the alloy block; although the density of the alloy block is slightly reduced after adding Cr powder compared with the As-Fe (0Cr) alloy block, it can still maintain a high density standard.
[0125] 2. Combined with the compressive strength test results, it can be seen that compared with the 0Cr alloy block, the compressive strength of the 5Cr alloy block is significantly increased; the compressive strength of the 20Cr alloy block reaches the highest value, which is more than 1 times higher than that of the 0Cr alloy block.
[0126] Further analysis results show that low Cr content can significantly improve the compressive strength of As-Fe (0Cr) alloy blocks, and the compressive strength of the alloy blocks is further improved with the increase of Cr content. From the XRD analysis results of the alloy blocks, it can be seen that the 20Cr alloy blocks are composed of a uniform, nearly single FeAs phase, and the Cr element is almost completely dissolved in the Fe element and the element is evenly distributed, forming a uniform microstructure, which may lead to the improvement of the compressive strength of 20Cr.
[0127] 3. Combined with the hardness test results, it can be seen that the hardness value of the 5Cr alloy block has decreased. When the Cr content in the ternary alloy block reaches 15wt.%, the hardness value of the 15Cr alloy block begins to rise, and the hardness value of the 20Cr alloy block continues to rise slightly.
[0128] The analysis shows that the change trend of hardness value is similar to that of actual density, which means that the change of hardness may be related to the factors affecting density; low Cr content may cause lattice distortion of alloy block or form FeAs 2 phase, which causes a decrease in hardness; with the increase of Cr content, the phase of the alloy block gradually transforms into a harder FeAs phase and the distribution of Cr elements becomes more uniform, thereby causing the hardness to rise; although the hardness of the 20Cr alloy block is lower than that of the 0Cr alloy block, it still shows a higher hardness value.
[0129] 4. Combined with the leaching toxicity test results, as shown in Table 1, the concentrations of As and Fe in the leachate of the 0Cr alloy block are relatively high; as the Cr content in the ternary alloy block (arsenic-iron based alloy) increases from 5wt.% to 15wt.%, the concentrations of As and Fe in the leachate of the ternary alloy block decrease significantly, and the Cr element is almost not leached, but the leaching concentration of the As element is still higher than the limit value of As in the "Identification of Hazardous Waste Identification Standard Leaching Toxicity Identification" (As: 5mg / L).
[0130] It is worth noting that when the Cr content in the ternary alloy block reaches 20wt.%, the As concentration in the 20Cr alloy block leachate is further reduced to 4.41mg / L, which is lower than the standard limit, indicating that the Cr content has a significant effect on the environmental stability of the alloy block.
[0131] In general, the As in the 20Cr alloy block can be effectively stabilized, and the leaching values of Fe and Cr are also low, which has minimal environmental pollution. It is worth noting that in the leaching solution of all ternary alloy blocks, the concentration of Cr is extremely low and is almost not leached.
[0132] The comprehensive analysis of the results shows that when the Cr content is greater than or close to 20wt.%, the heavy metals in the ternary alloy block can be stabilized well. This may be because when the Cr content in the alloy block is low, as it contacts the leaching agent, the low Cr concentration cannot form a dense oxide layer; as the Cr concentration in the alloy system increases, (Fe, Cr) will gradually form. 2 O 3 or FeFe 2-x Cr x O 4 Subscale oxide layer makes it difficult for elements in the alloy to be leached out. When the Cr concentration in the alloy reaches a certain value (20wt.%), the alloy block forms a dense Cr 2 O 3 The passivation film blocks the elements in the alloy from contacting the leaching solution, preventing further leaching; therefore, when the Cr content in the ternary alloy block is 20wt.%, the concentration values of each element in the 20Cr alloy block leaching solution are relatively low.
[0133] Table 1 Leaching concentration of As-Fe-xCr (x = 0, 5, 10, 15, 20 wt.%) ternary alloy block
[0134]
[0135] Analysis example 2
[0136] The As-Fe-xCr (5, 10, 15, 20 wt.%) ternary alloy blocks obtained in the above Examples 1-4 and the As-Fe (0Cr) alloy block obtained in Comparative Example 1 were leached by TCLP method and then tested for compressive strength and hardness. The compressive strength and hardness results of the alloy blocks after leaching are as follows: Fig.11 and Fig.12 shown.
[0137] The results show that the compressive strength of the 0Cr alloy block after leaching is low, which is 516.62MPa. With the increase of Cr concentration in the ternary alloy block, the compressive strength of the 5Cr, 10Cr, 15Cr and 20Cr alloy blocks after leaching are 801.65MPa, 975.50MPa, 1113.34MPa and 1345.37MPa respectively, and the compressive strength still shows an upward trend. The compressive strength of the 20Cr alloy sample reaches the highest value, which is more than twice the compressive strength of the 0Cr alloy block after leaching; compared with the compressive strength of the 20Cr alloy block before leaching, it is only reduced by about 7.0%. This phenomenon shows that the content of Cr element before and after leaching has a significant improvement on the compressive strength of the alloy block and can maintain a high compressive strength.
[0138] After leaching, the hardness of 0Cr, 5Cr, 10Cr, 15Cr and 20Cr alloy blocks are 736.33HV, 183.25HV, 298.53HV, 603.80HV and 844.65HV respectively. The results show that ( Fig.12 ), when the Cr concentration in the ternary alloy block is low, especially the 5Cr alloy block, the hardness decreases significantly after leaching, which may be attributed to the increase of pores on the surface of the alloy block after leaching and the increase of grain size, which leads to a significant decrease in hardness. When the Cr concentration increases further, the hardness increases, and the 20Cr alloy block shows a relatively high hardness of 844.65HV; it can be inferred that adding a certain amount of Cr element to the alloy helps to improve the hardness stability of the alloy. It is worth noting that the hardness of the 20Cr alloy after acid leaching is higher than that before leaching, which may be due to the generation of Cr on the surface of the alloy block. 2 O 3 Due to the phase, Cr 2 O 3 Nanoparticles can act as a hardening phase, thereby increasing the hardness value of the alloy bulk.
[0139] The results of comprehensive analysis of the mechanical properties of the alloy block after leaching show that 20Cr alloy has excellent mechanical properties and sufficient environmental stability, which makes it have great potential for industrial application. It is expected to be developed into a high-strength and environmentally stable arsenic-iron based multi-element alloy.
[0140] The above technical solutions of the present invention are only preferred embodiments of the present invention, and the patent scope of the present invention is not limited thereto. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for preparing a high-performance, compressive-stable arsenic-iron-based alloy, characterized in that: Includes steps: S1, providing a mixture; the mixture comprises arsenic iron powder and chromium powder, the arsenic iron powder comprises arsenic powder and iron powder; the mass percentage of the chromium powder and the arsenic iron powder is not less than 4%; S2, ball milling the mixture under the protection of an inert atmosphere to obtain a ball milling product; the ball milling time is not less than 8 hours; S3, vacuum hot pressing and sintering the ball milled product to obtain an arsenic-iron based alloy; the vacuum hot pressing and sintering comprises: in a vacuum environment, heating the ball milled product to 350-500°C for a heat preservation time of not less than 0.3h; then, heating the ball milled product to 600-850°C for a heat preservation time of not less than 0.5h; and, during the vacuum hot pressing and sintering process, applying a pressure of 25-50MPa to the ball milled product.
2. The method for preparing a high-performance, compressive-stable arsenic-iron-based alloy according to claim 1, characterized in that: The mass percentage of the chromium powder and the ferroarsenic powder is not less than 15%.
3. The method for preparing a high-performance, compressive-stable arsenic-iron-based alloy according to claim 2, characterized in that: The mass percentage of the chromium powder and the ferroarsenic powder is not less than 20%.
4. The method for preparing a high-performance, compressive-stable arsenic-iron-based alloy according to claim 1, characterized in that: The mass percentage of the chromium powder and the ferroarsenic powder is 4-21%.
5. The method for preparing a high-performance, compressive-stable arsenic-iron-based alloy according to claim 4, characterized in that: The mass percentage of the chromium powder and the ferroarsenic powder is 14-21% or 19-21%.
6. The method for preparing a high-performance, compressive-stable arsenic-iron-based alloy according to claim 1, characterized in that: The molar ratio of the arsenic powder to the iron powder is 0.1 to 2:
1.
7. The method for preparing a high-performance, compressive-stable arsenic-iron-based alloy according to claim 1, characterized in that: The rotation speed of the ball mill is 250-400 r / min, and the duration of the ball mill is 8-48 h.
8. The method for preparing a high-performance, compressive-stable arsenic-iron-based alloy according to claim 7, characterized in that: The ball-to-material ratio of the ball mill is 10 to 22:1; the particle size of the grinding balls used in the ball mill includes one or more of 3 mm, 6 mm, 10 mm and 15 mm.
9. A high performance, compressive and stable arsenic-iron based alloy, characterized in that: The preparation is carried out by the preparation method according to any one of claims 1 to 8.
10. The arsenic-iron based alloy according to claim 9, characterized in that: The physical phases in the arsenic-iron based alloy include an iron-chromium solid solution phase and FeAs.
Citation Information
Patent Citations
Arsenic-iron alloy, preparation method and resourceful treatment method
CN115491534A
High-strength, high-hardness and high-density arsenic-based alloy and preparation method thereof
CN118374711A